KAJIAN AFINITAS SENYAWA PERISA TERHADAP RESEPTOR ESTROGEN DAN ANDROGEN MENGGUNAKAN METODE KOMPUTASI SEBAGAI BAGIAN DARI EVALUASI KEAMANAN BAHAN TAMBAHAN PANGAN - Gloriana Ardianti, Sheila
Food additive should be proven to be safe based on experimental results. However, when experimental data is insufficient or not available, computational method can be applied to conduct safety assessment. The aim of this research was to obtain affinity data of several flavoring substances on androgen and estrogen receptors applying computational method. Registered flavoring substances were grouped according to their main functional group and 40 compounds were choosen as sample representing each group and subgroup. These compounds were docked on estrogen (PDB ID: 3ERT) and androgen (PDB ID: 3V49) receptors using AutoDock application. Ten compounds with the lowest estimated binding energy were further studied by means of molecular dynamics method conducted using AMBER software with MM/PBSA calculation approach. Tamoxifen as the reference compound of the estrogen receptor showed the dissociation constant (Ki) of 5.2808 x 10- 3 M and the 10 test compounds showed the Ki in the range of 1.4116 x 10- 10 M to 4.4683 x 102 M to this receptor. In the case of androgen receptor, 4-[(4R)-4-(4-hydroxyphenyl)-3,4-dimethyl-2,5-dioxoimidazolidine-1-yl]-2- (trifluoromethyl) benzonitrile as reference compound showed the Ki of 3.084 x 10- 6 M and the 10 test compounds showed the Ki in the range of 1.3622 x 10- 9 to 1.7547 x 10- 2 M to this receptor. Based on overall results, it was concluded that three out of ten compounds (cinnamyl cinnamate, gliceryl tribenzoate and 2-thienyl disulfide) showed higher affinity on the estrogen receptor compared to the reference compound, while in the case of androgen receptor only one (glyceryl monooleate) out of ten compounds showed higher affinity to this receptor compared to the reference compound.